Neuronal Cells Rearrangement During Aging and Neurodegenerative Disease: Metabolism, Oxidative Stress and Organelles Dynamic - Castelli, Vanessa; Benedetti, Elisabetta; Antonosante, Andrea; Catanesi, Mariano; Pitari, Giuseppina; Ippoliti, Rodolfo; Cimini, Annamaria; d’Angelo, Michele (Frontiers in Molecular Neuroscience, 2019)
Brain cells normally respond adaptively to the oxidative stress or bioenergetic challenges, resulting from ongoing activity in neuronal circuits. During aging and in neurodegenerative disorders, these mechanisms are compromised. In fact, neurons show unique age-related changes in function and metabolism, resulting in greater susceptibility to insults and diseases. Aging affects the cells in the nervous system much as do cells in other organ systems. More precisely, as the nervous system ages, neuron metabolism may change, inducing glucose hypometabolism, impaired transport of critical substrates underlying metabolism, alterations in calcium signalling, mitochondrial dysfunction and so on. Moreover, in neuronal aging an accumulation of dysfunctional and aggregated proteins and mitochondria is observed, as a result of an oxidative imbalance: reduced antioxidant defenses and/or increase of reactive oxygen species (ROS). These changes lead to greater vulnerability of neurons in various regions of the brain and increasing susceptibility to various diseases. In particular, in this review we will focus on neuronal cell rearrangement during aging, in response to changes in metabolism and oxidative stress.